RAZÕES DA LÍNGUA: CULTURA E ENSINO DE INGLÊS - Rubio, Juliana Bassani (2014)
Languages are phenomena connected with the human being and abilities created by the human societies. According to the American linguist, Noam Chomsky, when we study human language, we are approaching what some might call the human essence, the distinctive qualities of mind that are, so far as we know, unique to man. As well as Chomsky, the thinker Lev Vygotsky, supported the idea that languages serve essentially for the expression of thought. This study discusses the language teaching through a perspective that exceeds the simple learning (pronunciation, vocabulary, grammar etc), and also involves the analysis of cultural and anthropological factors as indicated by the philosopher Josef Pieper and the linguist David Crystal. After a theoretical analysis, the English language and its duality are analyzed.